HAK SYAFAAT DALAM AL-QUR’AN: Kajian Tematik dengan Pendekatan Epistemologi Bayani, Burhani, dan Irfani - Nadjamuddin Shiddiq, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the concept of syafaat (intercession) in the Qur’an through a thematic approach based on the epistemological framework of bayani, burhani, and irfani. This research responds to the phenomenon of misconceptions in Muslim communities where syafaat is often understood as an unconditional guarantee of salvation through the mediation of certain figures or rituals, which contradicts the principle of tawhid. Using a qualitative method with library research, the study systematically examines Qur’anic verses related to syafaat and interprets them comprehensively through three epistemological dimensions. The findings show that syafaat is a prerogative of Allah and only given to specific individuals with His permission and pleasure, reinforcing the principle of justice and mercy of Allah. The study also reveals the need to correct societal misunderstandings about syafaat, which often lead to passive and fatalistic attitudes that weaken the spirit of good deeds. Integrating the bayani, burhani, and irfani approaches provides a more holistic and moderate understanding of syafaat, preserving tawhid and fostering a balanced religiosity. This research contributes theoretically to thematic Qur’anic studies and practically to Islamic education, da’wah, and community guidance. Keywords: syafaat, Qur’an, bayani, burhani, irfani, epistemology, tawhid